Kedudukan Hukum Peraturan Desa (Perdes) dalam Hierarki Peraturan Perundang-undangan di Indonesia - Setiawan, Agus; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Village Regulations (Peraturan Desa or Perdes) serve as an attributive legal instrument for villages, yet their standing has sparked debate since their omission from the formal hierarchy under Article 7 Paragraph (1) of Law Number 12 of 2011 jo. Law Number 13 of 2022. Using a legal doctrinal approach with statutory, conceptual, and historical perspectives, this study analyzes the legal status, hierarchical relations, and legal implications of the current standing of Perdes. The results indicate that Perdes remain valid and binding legislation based on Article 8 of the aforementioned Law, as they are enacted through attributive authority. The position of Perdes is sui generis lying outside the formal hierarchy but remaining bound by the lex superior derogat legi inferiori principle. Consequently, their review relies on executive preview and executive review by Regents/Mayors, leaving a lacuna in comprehensive judicial review mechanisms at the Supreme Court.